2022
DOI: 10.1016/j.cjco.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and Long-term Risk of Stroke in Patients With Perioperative Atrial Fibrillation After Cardiac Surgery: Systematic Review and Meta-analysis

Abstract: Short-term and long-term risk of stroke in patients with perioperative atrial fibrillation after cardiac surgery: Systematic review and meta-analysis, CJC Open (2021), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 73 publications
1
30
1
2
Order By: Relevance
“…4 In a study investigating the effect of POAF in patients after cardiac surgery, long-term mortality rates in patients with post-cardiac surgical atrial fibrillation were reported to be significantly higher at 32.7%, 5 as compared with patients without post-cardiac surgical atrial fibrillation (22.4%). 5 Similarly, for patients who developed post-cardiac surgery atrial fibrillation, their incidence of experiencing major neurological events (MNEs) was 4.5%, 6 and the incidence of bleeding was 5%. 7 To counter the potentially disastrous sequelae of postcardiac surgical atrial fibrillation, anticoagulation therapy, primarily warfarin, is prescribed to the patient.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…4 In a study investigating the effect of POAF in patients after cardiac surgery, long-term mortality rates in patients with post-cardiac surgical atrial fibrillation were reported to be significantly higher at 32.7%, 5 as compared with patients without post-cardiac surgical atrial fibrillation (22.4%). 5 Similarly, for patients who developed post-cardiac surgery atrial fibrillation, their incidence of experiencing major neurological events (MNEs) was 4.5%, 6 and the incidence of bleeding was 5%. 7 To counter the potentially disastrous sequelae of postcardiac surgical atrial fibrillation, anticoagulation therapy, primarily warfarin, is prescribed to the patient.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…Perioperative atrial fibrillation (POAF) is the most common arrhythmia encountered after cardiac surgery, with the estimated incidence of new-onset POAF ranging between 24% and 49%. 1 Although POAF has been viewed as a benign and self-limited phenomenon, a growing body of evidence suggests that POAF is associated with an increased short-term and long-term risk of stroke and death. [1][2][3] Oral anticoagulation therapy is highly effective for the long-term prevention of ischemic stroke and systemic embolism in patients with nonsurgical atrial fibrillation (AF).…”
Section: R Esum Ementioning
confidence: 99%
“…1 Although POAF has been viewed as a benign and self-limited phenomenon, a growing body of evidence suggests that POAF is associated with an increased short-term and long-term risk of stroke and death. [1][2][3] Oral anticoagulation therapy is highly effective for the long-term prevention of ischemic stroke and systemic embolism in patients with nonsurgical atrial fibrillation (AF). 4 CJC Open -(2022) 1e8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gaudino and colleagues 2 estimated a pooled rate of stroke after cardiac surgery of 2.0%, which increased the risk of operative mortality (21.3% vs 2.4%) and the incidence rate of late mortality (10.9% vs 3.4%) compared with those who did not experience stroke. Diseased ascending aorta, 3 carotid artery stenosis, 4 previous stroke, 2 complex cardiac surgery, 5 prolonged cardiopulmonary bypass, 6 postoperative atrial fibrillation, 7 and blood transfusion 8 are recognized as risk factors for stroke after cardiac surgery.…”
mentioning
confidence: 99%